Hubungan Pengetahuan dengan Perilaku Ibu Hamil dalam Menjalani Kehamilan Selama Masa Pandemi Covid-19 - Mira Mira Rizkia (Jurnal Keperawatan Malang, 2020)
Background: Pregnancy, also known as the gestation phase, is a physiological process experienced by a woman. There are various factors that can influence a mother in undergoing her pregnancy including knowledge and behavior. Purose: The aim of this study was to determine the correlations between knowledge and behavior of mothers during pregnancy during the Covid-19 pandemic in Aceh. Method: This is a descriptive explorative research with cross sectional desain. There were 138 pregnant women who were selected as respondents by using the simple random sampling. Data analysis involved the use of the chi-square. Results: Showed that there was a relationship between knowledge and maternal behavior during pregnancy during the Covid-19 pandemic (p = .001). Recommendation: Therefore, the knowledge is an important factor for pregnant women because it can affect the mother's behavior during pregnancy. It is hoped that optimal education from health workers for mothers to be able to live their pregnancy in a prosperous manner so that mothers and fetuses remain healthy during the Covid-19 pandemic.